Respuesta :

Answer:

see explanation

Step-by-step explanation:

Using the rule of radicals

[tex]\sqrt{a}[/tex] × [tex]\sqrt{b}[/tex] ⇔ [tex]\sqrt{ab}[/tex], thus

[tex]\frac{ab}{c}[/tex]

= [tex]\frac{\sqrt{2}\sqrt{10}  }{\sqrt{5} }[/tex]

= [tex]\frac{\sqrt{20} }{\sqrt{5} }[/tex]

= [tex]\frac{\sqrt{4(5)} }{\sqrt{5} }[/tex]

= [tex]\frac{2\sqrt{5} }{\sqrt{5} }[/tex] ← cancel [tex]\sqrt{5}[/tex]

= 2

-----------------------------------------------------------------------------

(a)

Given

9[tex]\sqrt{3}[/tex] - 4[tex]\sqrt{3}[/tex] + [tex]\sqrt{5}[/tex] + 2[tex]\sqrt{5}[/tex]

Collect like radicals, that is

(9 - 4)[tex]\sqrt{3}[/tex] + (1 + 2)[tex]\sqrt{5}[/tex]

= 5[tex]\sqrt{3}[/tex] + 3[tex]\sqrt{5}[/tex]

(b)

Given

10[tex]\sqrt{2}[/tex] + 4[tex]\sqrt{7}[/tex] - 6[tex]\sqrt{2}[/tex]

Collect like radicals

= (10 - 6)[tex]\sqrt{2}[/tex] + 4[tex]\sqrt{7}[/tex]

= 4[tex]\sqrt{2}[/tex] + 4[tex]\sqrt{7}[/tex]